Przekład udomowiony — przekład wyobcowany - Spyrka, Lucyna (Przekłady Literatur Słowiańskich, 2011)
Domesticated translation — foreignizated translation In the theory of translation rooted terms: domesticated translation — foreignizated translation, They are used as the name of the translation strategies. The first of them consits in bringing the author to the reader; the second one — inversely — consists in bringing teh reader to the author. As a replacement are used the terms: exotic and naturalisation in translation. Tranlsation can be seen as a process and a product. Domestication and foreignization also can be understood as the concept of social, whoch relate to existence of tranlsation in the host culture.In this context domestication is not synonymous with acquaintance and it is inclusion of the work in the tradition of the host literature under the same conditions under which literary works are subject to activation of native with complementary the host culture of the text which intensive impacts on its development. Foreignization means the removal of the host culture of the translation, which had already been domesticated in this culture or which was in a situation of translation — guest or which never existed in the host literature, although it has been published. Choice strategy, nor the quality of translation is not always decide od the domestication and foreignization of translation in the host culture. The domestication largely determines the need for the secondary culture of the text. The foreignization may be come with errors in tranlsation but also with a number of factors, which are outside the lyric, independent of the interpretation. The article discusses the specific cases of domestication and foreignization of translation, mainly in Polish — Slovak interliterature communication.